Allele specific expression in worker reproduction genes in the bumblebee Bombus terrestris - Harindra E. Amarasinghe; Bradley J. Toghill; Despina Nathanael; Eamonn B. Mallon (PeerJ, 2015)
Methylation has previously been associated with allele specific expression in ants. Recently, we found methylation is important in worker reproduction in the bumblebee Bombus terrestris. Here we searched for allele specific expression in twelve genes associated with worker reproduction in bees. We found allele specific expression in Ecdysone 20 monooxygenase and IMP-L2-like. Although we were unable to confirm a genetic or epigenetic cause for this allele specific expression, the expression patterns of the two genes match those predicted for imprinted genes.